2007
DOI: 10.1080/17470910601043644
|View full text |Cite
|
Sign up to set email alerts
|

Spatial statistics of gaze fixations during dynamic face processing

Abstract: Social interaction involves the active visual perception of facial expressions and communicative gestures. This study examines the distribution of gaze fixations while watching videos of expressive talking faces. The knowledge-driven factors that influence the selective visual processing of facial information were examined by using the same set of stimuli, and assigning subjects to either a speech recognition task or an emotion judgment task. For half of the subjects assigned to each of the tasks, the intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
162
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(173 citation statements)
references
References 44 publications
8
162
3
Order By: Relevance
“…This pattern is confirmed in our finding that the eyes were indeed looked at most frequently. When auditory noise is added to the speech, or when the task requires accurate auditory discriminations, a higher frequency of fixations are made to the mouth (Buchan, Pare, & Munhall, 2007). Intriguingly, deaf people also tend to look at the eyes of others communicating with sign language, although beginners also look at the mouth (Emmorey, Thompson, & Colvin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is confirmed in our finding that the eyes were indeed looked at most frequently. When auditory noise is added to the speech, or when the task requires accurate auditory discriminations, a higher frequency of fixations are made to the mouth (Buchan, Pare, & Munhall, 2007). Intriguingly, deaf people also tend to look at the eyes of others communicating with sign language, although beginners also look at the mouth (Emmorey, Thompson, & Colvin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These studies, however, often use a free-viewing task, which lacks a specific task context, to test non-pet-owners. Given that our gaze allocation in face exploration is subject to a modulatory role of task-based top-down guidance (Buchan, Pare, & Munhall, 2000;Malcolm, Lanyon, Fugard, & Barton, 2008), it remains unclear whether our enhanced experience with non-conspecific faces (e.g., pet owners) would influence our gaze allocation for extracting salient facial cues and/or facilitate the subsequent processing of specific facial information.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the active visual exploration of dynamic faces has only been investigated during audiovisual and visual-only speech perception (e.g. Vatikiotis-Bateson et al, 1998;Lansing & McConkie, 1999, 2003Paré et al, 2003;Buchan et al, 2007;Everdell et al, 2007) and so it is still unknown how an explicit identity task using dynamic facial stimuli might influence gaze behavior.A second, related possibility for the difference in mouth fixations is that the identity of a talking face is not restricted to the visual modality. Voices also contain information about identity and gaze fixations may be tuned to maximize the audiovisual integration of this information.…”
mentioning
confidence: 99%
“…The knowledge driven nature of gaze fixations is also evident in the gaze behaviors exhibited while watching talking faces. Gaze behavior studies examining audiovisual (Buchan, Paré & visual-only (Lansing &McConkie, 1999) speech have shown that task instructions influence facial locations from which information is gathered.The influence of task instructions on gaze behavior, however, is surprisingly modest (Buchan, Paré & Munhall, 2007;Lansing & McConkie, 1999). While task instructions cause a slight shift in the preferred fixation locations on the face, the overall spatial distribution of fixations nonetheless remains fairly similar across tasks.…”
mentioning
confidence: 99%
See 1 more Smart Citation